On the potential use of the Ecosystem Services Valuation Database for valuation in the System of Environmental Economic Accounting - Luke Brander; Jan Philipp Schägner; Rudolf de Groot (One Ecosystem, 2022)
The System of Environmental Economic Accounting - Ecosystem Accounting (SEEA EA) provides a framework for quantifying and valuing ecosystem services that is consistent with the System of National Accounts (SNA). As such, monetary estimates for ecosystem services are required to be measured as exchange values. The environmental economics literature on the value of ecosystem services has expanded consideralby over the past two decades and the Ecosystem Services Valuation Database (ESVD) currently provides the most comprehensive collection and synthesis of this information. The primary valuation studies included in the ESVD, however, measure a variety of value concepts including welfare values, exchange values and others. This raises a challenge for using existing value data as input to SEEA EA applications. This paper explores potential approaches to using the ESVD for value transfers that are consistent with SEEA EA, specifically for the estimation of meta-analytic value functions that can be used to reflect spatial variation in supply and demand of ecosystem services and proxy exchange values. It identifies avenues for future research and development of the ESVD to operationalise and test this approach.